2018
DOI: 10.1080/02640414.2018.1532546
|View full text |Cite
|
Sign up to set email alerts
|

Performing pull-ups with small climbing holds influences grip and biomechanical arm action

Abstract: Pull-ups are often used by sport-climbers and other athletes to train their arm and back muscle capabilities. Sport-climbers use different types of holds to reinforce finger strength concomitantly. However, the effect of grip types on pull-up performance had not previously been investigated. A vertical force platform sensor measured the force exerted by climbers when performing pull-ups under six different grip conditions (gym-bar, large climbing hold, and four small climbing holds: 22mm, 18mm, 14mm, and 10mm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
1
22
0
2
Order By: Relevance
“…Interestingly, both groups demonstrated a similar utilization rate in the ledge condition relative to the jug condition (57–69% of jug results), suggesting that despite boulder climbers being stronger in the prime movers, both groups are equally limited by finger strength when testing on a smaller hold. These results support previous findings that the hold size and shape is a crucial factor for performance in climbing-specific tests [20].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, both groups demonstrated a similar utilization rate in the ledge condition relative to the jug condition (57–69% of jug results), suggesting that despite boulder climbers being stronger in the prime movers, both groups are equally limited by finger strength when testing on a smaller hold. These results support previous findings that the hold size and shape is a crucial factor for performance in climbing-specific tests [20].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is generally accepted that finger flexor strength is a crucial factor for performance in climbing and climbing-specific tests [3, 5, 1221]. For example, Vigouroux et al [20] demonstrated that smaller climbing holds have a negative impact on force and power output in addition to number of pull-ups to failure among elite climbers. To the authors’ knowledge, however, no previous studies have examined the percentage of isometric force generated by the prime movers that can be utilized on a ledge hold (high level of finger strength requirement) compared to a jug hold (very low level of finger strength requirement).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although technical and mental factors certainly contribute to climbing outcomes (Baláš et al, 2014;Watts, 2004), it is widely accepted that strength and endurance of the upper-body is the primary predictor for climbing performance (Baláš et al, 2012;Mermier, 2000;Philippe et al, 2012;Quaine et al, 2003;Saul et al, 2019;Vigouroux and Quaine, 2006). Specifically, high levels of maximal and explosive strength of the fingers and forearms, elbow flexors, and shoulder-and back muscles (pulling apparatus) have been identified as significant attributes of highly accomplished climbers (Deyhle et al, 2015;Grant et al, 2001;Laffaye et al, 2014;Levernier and Laffaye, 2019b;Vigouroux et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Aspek kekuatan dan power tersebut sangat menunjang terhadap kemampuan teknik yang dimilik atlet (Abade et al, 2019;Thiele et al, 2020). Dalam olahraga hockey berbagai macam teknik yang harus dimiliki diantara lain adalah teknik push, tapping, hit, stop, scoop, flick, maupun dribbling (Barth & Nordmann, 2007).Agar semua teknik ini dapat dilakukan dengan baik oleh atlet, maka selain latihan drill yang berfokuskan pada (Prayadi & Rachman, 2013;Vigouroux et al, 2019).…”
unclassified